Rekonseptualisasi Pendidikan Agama Kristen di Tengah Arus Sekularisasi Modern - Harun Puling; Sandra Rosiana Tapilaha (Kharisma: Jurnal Ilmiah Teologi, 2026)
AbstractThe modern wave of secularization has shifted human value orientation from spirituality toward rationality and materialism, resulting in a crisis of meaning that diminishes the role of Christian Religious Education (CRE) as a formative agent of faith and spiritual character. This study aims to theologically and philosophically analyze a reconceptualization model of CRE that integrates faith and modern rationality through a qualitative–theological approach employing literature analysis and contextual hermeneutics. The research is grounded in Stephen Bevans’ framework of contextual theology, particularly the praxis model, which emphasizes a dynamic interaction between theological reflection and social reality as the locus of faith’s actualization. The findings indicate that secularization, in light of the theology of common grace and divine providence, is not a threat but rather a space for God’s participation in human history through the missio Dei. Consequently, the renewal of Christian Religious Education should focus on integrating faith and knowledge, reflective-dialogical learning, and contextual praxis spirituality, so that religious education functions as a prophetic force amid the current of secularization. AbstrakArus sekularisasi modern telah menggeser orientasi nilai manusia dari spiritualitas menuju rasionalitas dan materialisme, menyebabkan krisis makna yang menurunkan peran Pendidikan Agama Kristen (PAK) sebagai pembentuk iman dan karakter rohani. Penelitian ini bertujuan menganalisis secara teologis dan filosofis model rekonseptualisasi PAK yang mampu mengintegrasikan iman dan rasionalitas modern melalui pendekatan kualitatif-teologis dengan analisis pustaka dan hermeneutik kontekstual. Kajian ini berlandaskan pada kerangka teologi kontekstual Stephen Bevans, khususnya praxis model, yang menekankan interaksi dinamis antara refleksi teologis dan realitas sosial sebagai ruang aktualisasi iman. Hasil penelitian menunjukkan bahwa sekularisasi, dalam terang teologi anugerah umum dan providensia Allah, bukan ancaman melainkan ruang partisipasi Allah dalam sejarah manusia melalui missio Dei. Pembaruan Pendidikan Agama Kristen diarahkan pada integrasi iman dan ilmu, pembelajaran reflektif-dialogis, serta spiritualitas praksis yang kontekstual, sehingga pendidikan agama berfungsi sebagai kekuatan profetis di tengah arus sekularisasi.